Identification of Partner Proteins of the Algae Klebsormidium nitens NO Synthases: Toward a Better Understanding of NO Signaling in Eukaryotic Photosynthetic Organisms - Chatelain, Pauline; Astier, Jeremy; Wendehenne, David; Rosnoblet, Claire; Jeandroz, Sylvain (Frontiers in Plant Science, 2021)
In animals, NO is synthesized from L-arginine by three isoforms of nitric oxide synthase (NOS) enzyme. NO production and effects have also been reported in plants but the identification of its sources, especially the enzymatic ones, remains one of the critical issues in the field. NOS-like activities have been reported, although there are no homologs of mammalian NOS in the land plant genomes sequenced so far. However, several NOS homologs have been found in algal genomes and transcriptomes. A first study has characterized a functional NOS in the chlorophyte Ostreococcus tauri and the presence of NOS homologs was later confirmed in a dozen algae. These results raise the questions of the significance of the presence of NOS and their molecular diversity in algae. We hypothesize that comparisons among protein structures of the two KnNOS, together with the identification of their interacting partner proteins, might allow a better understanding of the molecular diversification and functioning of NOS in different physiological contexts and, more generally, new insights into NO signaling in photosynthetic organisms. We recently identified two NOS homologs sequences in the genome of the streptophyte Klebsormidium nitens, a model alga in the study of plant adaptation to terrestrial life. The first sequence, named KnNOS1, contains canonical NOS signatures while the second, named KnNOS2, presents a large C-ter extension including a globin domain. In order to identify putative candidates for KnNOSs partner proteins, we draw the protein–protein interaction networks of the three human NOS using the BioGRID database and hypothesized on the biological role of K. nitens orthologs. Some of these conserved partners are known to be involved in mammalian NOSs regulation and functioning. In parallel, our methodological strategy for the identification of partner proteins of KnNOS1 and KnNOS2 by in vitro pull-down assay is presented.